The Influence of Media Literacy and Attitude Change on Religious Moderation among Millennial Generation in Bone Regency - St. Rabiyatul Adawiah Nur; Arifuddin Tike; Kamaluddin Tajibu (Jurnal Mercusuar, 2022)
This study aims to analyze the level of influence of media literacy on religious moderation among the millennial generation; analyze the level of influence of attitude change on religious moderation among the millennial generation; and analyze the simultaneous influence of media literacy and attitude change on religious moderation among the millennial generation in Bone Regency. This research is quantitative with an explanatory method. The population in this study is the millennial generation in Bone Regency, especially those in Tanete Riattang Barat District, totaling 35,917 people, with a sample of 359 people using purposive sampling. The results show that: 1) The level of media literacy understanding among the millennial generation is in the moderate category, with a frequency of 209 respondents and a percentage of 58%. Additionally, media literacy has a positive and significant effect on religious moderation among the millennial generation in Bone Regency, with a regression coefficient of 0.215 and a sig value < 0.05. 2) The level of attitude change among the millennial generation is in the moderate category, with a frequency of 205 respondents. Moreover, attitude change has a significant effect on religious moderation among the millennial generation in Bone Regency, with a regression coefficient of 0.799 and a sig value < 0.05. 3) Media literacy and attitude change simultaneously have a significant effect on religious moderation among the millennial generation in Bone Regency, with an F value of 49.390. This means that the better the level of understanding and media literacy skills possessed by the millennial generation and the greater the attitude change they have, the higher the level of religious moderation will be.